Thermal management of helicopter sub-system in various states of flight - Surmacz, K.; Dziubi?ski, A.; Hirsch, F. (My University, 2019)
The paper describes the aerothermodynamic analysis of the conceptual design of the modern helicopter SH09 developed by the Kopter Group AG. For better understanding of the cooling process in the helicopter, Computational Fluid Dynamics tools were used. The object of research was the internal flow in the space under the cowl of a helicopter. The simulation also takes into account the external influence, including the downwash from the main rotor of a helicopter. The CFD analysis of the SH09 helicopter concerned different states of flight and their impact on the cooling process. The results of the helicopter operating in several conditions such as: hover, forward, rearward and lateral flight are presented. The aim of the computational investigation was to find out key parameters of cooling process of the helicopter, in particular: the main directions of flow in different conditions of a helicopter flight, the airflow cooling under normal and extreme conditions, the impact of the flight conditions, ambient conditions and oil cooler fan setting, the efficiency of the cooling system.